2016
DOI: 10.1063/1.4943296
|View full text |Cite
|
Sign up to set email alerts
|

Multistability of phase-locking and topological winding numbers in locally coupled Kuramoto models on single-loop networks

Abstract: Determining the number of stable phase-locked solutions for locally coupled Kuramoto models is a long-standing mathematical problem with important implications in biology, condensed matter physics and electrical engineering among others. We investigate Kuramoto models on networks with various topologies and show that different phase-locked solutions are related to one another by loop currents. The latter take only discrete values, as they are characterized by topological winding numbers. This result is generic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 36 publications
0
66
0
Order By: Relevance
“…Refs. 12 and 28 on singlecycle networks were complemented by our recent work, 16 which showed that the bound N ≤ 2 · Int[n/4] + 1 is still valid for nonoriented coupling, even when one angle difference exceeds π/2, and that no stable fixed point exists with more than one angle difference exceeding π/2 for single-cycle networks. These results are summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Refs. 12 and 28 on singlecycle networks were complemented by our recent work, 16 which showed that the bound N ≤ 2 · Int[n/4] + 1 is still valid for nonoriented coupling, even when one angle difference exceeds π/2, and that no stable fixed point exists with more than one angle difference exceeding π/2 for single-cycle networks. These results are summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, we amplify on our earlier work 16 17 can only take discrete values, because angles are defined modulo 2π. As a matter of fact, single-valuedness of angle coordinates requires that summing over angle differences around any cycle in the network on which Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations